Electrochemical Stability Window of Imidazolium-Based Ionic Liquids as Electrolytes for Lithium Batteries - Kazemiabnavi, Saeed; Zhang, Zhengcheng; Thornton, Katsuyo; Banerjee, Soumik (The journal of physical chemistry. B, 2016)
This paper presents the computational assessment of the electrochemical stability of a series of alkyl methylimidazolium-based ionic liquids for their use as lithium battery electrolytes. The oxidation and reduction potentials of the constituent cation and anion of each ionic liquid with respect to a Li+/Li reference electrode were calculated using density functional theory following the method of thermodynamic cycles, and the electrochemical stability windows (ESW)s of these ionic liquids were obtained. The effect of varying the length of alkyl side chains of the methylimidazolium-based cations on the redox potentials and ESWs was investigated. The results show that the limits of the ESWs of these methylimidazolium-based ionic liquids are defined by the oxidation potential of the anions and the reduction potential of alkyl-methylimidazolium cations. Moreover, ionic liquids with [PF6]− anion have a wider ESW. In addition to characterizing structure–function relationships, the accuracy of the computational approach was assessed through comparisons of the data against experimental measurements of ESWs. The potentials calculated by the thermodynamic cycle method are in good agreement with the experimental data while the HOMO/LUMO method overestimates the redox potentials. This work demonstrates that these approaches can provide guidance in selecting ionic liquid electrolytes when designing high-voltage rechargeable batteries.